Immunodiagnosis Infeksi Aeromonas hydrophila pada Ikan - Yuli Purwandari Kristianingrum; Sitarina Widyarini; Kurniasih Kurniasih; Bambang Sutrisno; Charles Rangga Tabbu; Sugiyono Sugiyono (Jurnal Sain Veteriner, 2018)
Aeromonas hydrophila causes a disease that often infects fish and is known as Motile Aeromonas Septicaemia (MAS), Hemorrhagi Septisemia, Ulcer disease or Red-Sore disease. The   aims of this study were to develop polyclonal antibody of  Aeromonas hydrophila in the rabbits to   confirm the diagnosis of Aeromonas hydrophila  in the fish by immunohistochemistry staining method. Preparation of polyclonal antibodies was performed on the rabbits used to Aeromonas hydrophila bacteria that have been tested biochemically by intravenous and intraperitoneal injection. Doses of Aeromonas hydrophila  bacteria were 109 CPU/ml  of 0.5 ml at first injection, 1 ml at second injection, 2 ml at thirth injection and 3 ml at fourth injection. Blood serum collection was performed at week 5 after injection from  an  ear and intracardial vein. The result of antibody titer was 28 = 1024 which measured by   tube test. Furthermore, polyclonal   antibody was used to immunohistochemistry  staining with 400x dilution. The results of the staining showed that an immunopositive reaction in the liver, skin,lien,  gill, kidney, and heart of fish to Aeromonas hydrophila antibody. The research conclution was polyclonal antibody from rabbit can be used to accurately confirm the diagnosis of Aeromonas hydrophila  based on antigen and antibody reaction.